2012
DOI: 10.1095/biolreprod.112.102830
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Vascular Development in Early Mouse Decidua and Its Association with Leukocytes and Trophoblasts1

Abstract: In species with endometrial decidualization and hemochorial placentation (humans, mice, and others), leukocytes localize to early implant sites and contribute to decidual angiogenesis, spiral arterial remodeling, and trophoblast invasion. Relationships between leukocytes, trophoblasts, and the decidual vasculature are not fully defined. Early C57BL/6J implant sites were analyzed by flow cytometry to define leukocyte subsets and by whole-mount immunohistochemistry to visualize relationships between leukocytes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 52 publications
3
101
0
Order By: Relevance
“…4). Interestingly, neutrophilia has also been observed in human pregnancies (at 11215 wk), as well as in pregnancies of other mouse strains (10,55), which strongly implies a significant role of neutrophils in this period of pregnancy. In fact, neutropenic patients (low neutrophils) have higher spontaneous miscarriage rates (26%).…”
Section: Discussionmentioning
confidence: 80%
“…4). Interestingly, neutrophilia has also been observed in human pregnancies (at 11215 wk), as well as in pregnancies of other mouse strains (10,55), which strongly implies a significant role of neutrophils in this period of pregnancy. In fact, neutropenic patients (low neutrophils) have higher spontaneous miscarriage rates (26%).…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, studies of mouse uterine NK cells showed an increase in the inhibitory receptor KLRG1 with gestational age. 59 KLRG1 is a marker of senescence in mouse and human NK and T cells and is thought to block proliferation by interfering with Akt activation. 60 Thus, there is indirect evidence of a senescent phenotype of the mouse uterine NK cells during the key period of remodeling to permit placental blood flow.…”
Section: A Role For Senescence In Reproductionmentioning
confidence: 99%
“…Gd6.5 uterine horns (n52 pregnancies/genotype) were transected and stained with reagents listed in Table 1 as live, intact tissue as previously described. 32 Specimens were examined and photographed after 60 min using epifluorescence microscopy (Axiovision computer software; Zeiss Axiocam).…”
Section: Morphological Analysesmentioning
confidence: 99%